Brunei Darussalam : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2011)
The statistical appendices present the following details for Brunei Darussalam: Nominal GDP and quarterly nominal GDP by economic activity, nominal GDP and quarterly nominal GDP by expenditure, quarterly composition of nominal GDP and composition of nominal GDP by activity, real GDP and quarterly real GDP by economic activity and expenditure, oil and gas production and sales, consumer price index, imports and exports by commodities, country destination exchange rates, energy sector, financial soundness indicators, balance of payments, depository corporations survey, Brunei currency, and the monetary board survey.